2016
DOI: 10.1016/j.ijid.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic hepatitis B virus infection in Thailand: a systematic review and meta-analysis

Abstract: The high burden of CHB in Asian countries is a major challenge for the incorporation of national programs to prevent CHB complications within health care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 38 publications
7
36
2
2
Order By: Relevance
“…In this review, though the overall pooled prevalence estimate (6%) showed a slight decrement compared to the previous estimation (7.4%) [91], it is still a burden that represents an additional challenge for the national health system which is already fighting with the different infectious and noninfectious disease. In comparison to other studies conducted elsewhere, the result was more or less comparable to a finding from Thailand 5.1% [92]. However, it was significantly exceeded the global estimation (3.61%) and a finding from Though the pooled prevalence (4%) of HBV among blood donors was significantly decreased compared to the previous estimate 8.4% [91], our study raised concerns on strict adherence of safe blood supply in Ethiopia as 1 in 25 (4%) blood donors might be infected with the virus.…”
Section: Discussionsupporting
confidence: 82%
“…In this review, though the overall pooled prevalence estimate (6%) showed a slight decrement compared to the previous estimation (7.4%) [91], it is still a burden that represents an additional challenge for the national health system which is already fighting with the different infectious and noninfectious disease. In comparison to other studies conducted elsewhere, the result was more or less comparable to a finding from Thailand 5.1% [92]. However, it was significantly exceeded the global estimation (3.61%) and a finding from Though the pooled prevalence (4%) of HBV among blood donors was significantly decreased compared to the previous estimate 8.4% [91], our study raised concerns on strict adherence of safe blood supply in Ethiopia as 1 in 25 (4%) blood donors might be infected with the virus.…”
Section: Discussionsupporting
confidence: 82%
“…Estos resultados, particularmente en el caso de los jóvenes, pueden tener relación con la incorporación de la vacuna contra la hepatitis B como parte del programa de inmunización en la década de los 90. La vacuna contra la hepatitis B se ha traducido en reducción importante en la prevalencia de HBsAg (19) ; sin embargo, el efecto no sería muy favorable en escenarios donde la cobertura de la vacuna contra HVB es deficiente (20) .…”
Section: Discussionunclassified
“…These cases are most commonly caused by HBV infection (73.6%) [9]. The under-recognition of hepatitis B infection and poor adherence to surveillance program in those diagnosed with hepatitis B result in high prevalence rates [10,11].…”
Section: Chronic Hepatitis B Virus (Hbv) Infection Is Endemic Inmentioning
confidence: 99%